A new species of marine gobiid fish genus Lubricogobius (Teleostei: Gobiidae) from the Philippines - Chen, I-Shiung; Liao, Yun-Chih; Ho, Lin-Tai; Shao, Kwang-Tsao (Zootaxa, 2024)
A new marine goby of genus, Lubricogobius Tanaka, 1915 was collected from the Philippines. This new species, Lubricogobius rubrofasciatus n. sp., can be distinguished from other congeneric species by following unique combination of features: (1) second dorsal fin I/10; anal fin I/7; pectoral fin 18; (2) head and trunk entirely naked; (3) both anterior and posterior nostrils as short tubes; (4) gill opening large, extending ventrally beyond the rear vertical of peropercle; (5) infraorbital papillae all belonging to longitudinal pattern; and (5) colouration in life: body and head creamy white to yellow; iris bright orange; an oblique bright red orange stripe from nape to upper lip through eye; dorsal, anal, pelvic and caudal fins all with yellow to orange with wide, distal deep black margin. The description of new species and a diagnostic key to all congeners in the Indo-Pacific region will be reported in this paper.